Business Studies Pondoh Plants in Sand Nagari Binjai Kecamatan Silaut Kabupaten Pesisir Selatan - Lestari, Lestari; Erita, Yeni; U, Iswandi (Pendidikan Geografi, 2013)
Silaut Nagari is one of the transmigration areas in West Sumatera that were previously identified by a wilderness area that has a population of relatively small, so that the mixture of the Minang people and Javanese. At the present time the villages Silaut livelihood besides there is also a garden of palm plantation livelihoods barking. In general, people gardening bark is derived from the Javanese transmigration undertaken by the former government. This study aimed to obtain the data, process, analyze and discuss the study of crop enterprises in Nagari Pasir Binjai Kecamatant Silaut Kabupaten Pesisir Selatan in view of: 1) Plant nurseries Pondoh 2) Preparation of planting Pondoh 3) Treatment plants Pondoh 4) Fertilizing plants Pondoh 5) Harvest time Pondoh 6) Labor 7) Sources of capital plant Pondoh 8) The level of production of the crop Pondoh 9) Marketing efforts Pondoh plants.This study classified as descriptive research, the population in this study were all families (KK) pondoh salak farmers in Nagari Pasir Binjai Kecamatan Silaut Kabupaten Pesisir Selatan. The samples were taken with a total sampling technique, the sample numbered 56 families (KK). Collecting data using an open questionnaire, an analysis that is in use is descriptive statistics using the percentage formula.The results showed: 1) Plant nurseries Pondoh done in vegetative and generative (55.4%), the type of plants used are bark barking pondoh (100%). 2) Preparation penanamna using water pool but only partially (32.1%) and farmers generally use drainage (94.6%). 3) Treatment, farmers generally do cluster thinning (96.4%), weeding bunches (91.0%), pengemburan land (89.3%). 4) fertilization, the type of fertilizer used is usually organic and inorganic fertilizers (85.7%). Way is to sprinkle fertilizer fertilizer around the plants (92.8%). 5) harvest, yields 2-4 times a month (78.6%), how to select a crop that is picked (87.5%). 6) labor, generally numbered 2-5 people (75%). Age farmers generally >45 years (42.9%). 7) used the equity capital of Rp. >5 million to 10 million (51.8%), 8) production, the average number of production 1 acre 1 year ie >5-8 tonnes (62.5%), and the average number of production acres 1 Â½ years ie 2-5 tonnes (64.3%). 9) the average marketing price offered 1 kg Rp. 9000-12000 (89.3%), retail marketing system done and the bulk (84.0%).